The identification and functional characterisation of caspase substrates involved in inflammation - Luthi, Alexander U. (Trinity College (Dublin, Ireland). Department of Genetics, 2010)
During inflammation the immune system responds to harmful stimuli, tries to control the stimuli and initiate a healing process for damaged tissue. After recognition of microbes by the innate immune system caspases are activated and are required to activate cytokines. Human caspases have been studied for over two decades with most work in the field focused on apoptotic caspases. As a result hundreds of apoptotic caspase substrates have been identified to date, but only 2 inflammatory caspase substrates have been confirmed. Identification of novel targets for the caspases activated during the inflammatory process could provide new insights into the molecular mechanism of host defense, identify important immuno-regulatory molecules and targets for anti-inflammatory drug development.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin.